2017
DOI: 10.3892/ol.2017.5990
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-24 inhibits osteosarcoma cell migration and invasion via the JNK/c-Jun signaling pathways

Abstract: Abstract. Approximately 25% of osteosarcoma patients present with clinically detectable metastatic disease at the time of initial diagnosis. High-dose chemotherapy and/or surgery for the treatment of primary metastatic osteosarcoma is ineffective, and <20% of patients will survive 5 years from diagnosis. Therefore, the treatment of metastases is critical for the improvement of the prognosis of primary metastatic osteosarcoma patients. We have previously observed that overexpression of interleukin-24 (IL-24) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…A number of studies have demonstrated that JNK and ERK transcriptionally regulate the expression of MMP‐2 and MMP‐9, which results in regulation of cell migration and invasion . IL‐24 was overexpressed in osteosarcoma 143B cells through the activation of JNK/c‐Jun was inhibited and downregulation of MMP‐2 and MMP‐9 expression . Our results are consistent with the above studies, and we demonstrated that the sustained activation of ERK1/2 or JNK1/2 and the inhibition of MMP‐2 and MMP‐9 were involved in the β‐mangostin‐inhibited migration and invasion in HCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have demonstrated that JNK and ERK transcriptionally regulate the expression of MMP‐2 and MMP‐9, which results in regulation of cell migration and invasion . IL‐24 was overexpressed in osteosarcoma 143B cells through the activation of JNK/c‐Jun was inhibited and downregulation of MMP‐2 and MMP‐9 expression . Our results are consistent with the above studies, and we demonstrated that the sustained activation of ERK1/2 or JNK1/2 and the inhibition of MMP‐2 and MMP‐9 were involved in the β‐mangostin‐inhibited migration and invasion in HCC cells.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have indicated that the MAPK signal pathway plays a vital role in regulating the enzyme activity and protein expression of MMPs . Our results have revealed that kaempferol‐treated ARPE‐19 cells can phosphorylate ERK1/2 (Figure A) as well as decrease the expression and activity of MMP‐2 (Figure A,C).…”
Section: Discussionsupporting
confidence: 51%
“…Both assays revealed a stronger effect of the C3G + DDP combination on HeLa cells than that by the corresponding single treatments. Previous studies have shown that phytochemicals such as daphnoretin and grape seed extracts inhibited the migration and invasion of tumor cells (Meo et al, 2019;Yu et al, 2019), which may hinder cancer development and improve response to treatment (Zhuo et al, 2017). Polyphyllin I inhibits the growth and invasion of DDP-resistant gastric cancer cells (Zhang et al, 2018).…”
Section: Effects Of C3g Ddp and Their Combination On Invasion And Migration Of Hela Cellsmentioning
confidence: 99%